Situation Report: Poland, 21 January 1983 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The 1983 Annual National Plan The Sejm's Socioeconomic Council: A Collective Ombudsman Polish Style? A Cardinal's Hat for Poland's Primate / by Anna Swidlicka A Profile of Stanislaw Stomma / by Anna Swidlicka A Sorry Start for the Government-Sponsored Unions / by Anna Swidlicka